POLITICAL COMMUNICATION STRATEGIES OF NEW POLITICAL PARTY: A CASE STUDY OF INDONESIAN SOLIDARITY PARTY (PSI) - Karim Suryadi; Vidi Sukmayadi; Nursita Saria (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
Digital media is one of the most popular media communication in recent years. A number of communities and organizations commonly use digital media as vessels to communicate, to inform and disseminate information. The proliferation of digital media has also been eclipsed by a number of political parties to deliver political messages to the public. The high profit derived from the use of digital media gave the political party a new innovation. The Indonesian solidarity party (psi), as a new political party in Indonesia, tries to use digital media as its political means of communication. The research will focus on psi's political communication strategy asa new political party to market its products and parties in digital media. The approach used was qualitative by case study methods with in-depth interviews and for the selection of informants used a intergalactic sampling technique. The principal informers of the study are the leaders, stewards, and caddis of the psi and are supported by supporting experts in political communication, public and political rival psi. The study will further expose digital political communication strategies done by the psi to marketing products, parties, approaches to voters, parliament, internal and media. The results of this study suggest that digital media is particularly influential in the strategies used. Keywords: Communication strategy, digital media, Indonesian Solidarity Party